Agreement between center of disease control and word health organization reference growth - Silva, Cláudia Aparecida Arcari; Pereira, Maria José Bistafa; Nakano, Ana Márcia Spanó; Gomes, Flávia Azevedo; Silva, Isilia Aparecida (Revista da Escola de Enfermagem da USP, 2011)
The objective this study was to verify the agreement of the guidelines recommended by CDC and WHO to evaluate the nutritional state. This is a cross-sectional study, which counted with the participation of 254 children of ages 3 to 11 months and 29 days from São Paulo and Ribeirão Preto, performed from June 2005 to July 2006. The anthropometric indexes were obtained using the software available on the CDC and WHO websites. The Kappa Test was used for nominal variables (length/age) and weighted-Kappa for ordinal variables (weight/length). It was found that there are differences between the CDC and WHO guidelines regarding the evaluation of child nutrition, with greater differences in the results for children of ages 3 to 6 months.